A136 A LONGITUDINAL STUDY EXAMINING FODMAP INTAKE AND THE METABOLOME IN IBS PATIENTS. (15th March 2019) - Tuck, C J; Bennet, S M; Rolland, S; Reed, D E; Lopez Lopez, C D; Jaramillo Polanco, J O; Jiménez-Vargas, N N; Morissette, C; Beyak, M J; Ropeleski, M; Hassanzadeh Keshteli, A; Madsen, K; et al.
Abstract: Background: The low FODMAP (fermentable oligo-, di-, mono-saccharides and polyols) diet has proven efficacy to reduce symptoms of irritable bowel syndrome (IBS). Whilst some mechanisms of action are known, our previous work has suggested that FODMAP-microbiota interactions change the metabolome which may modulate pain signaling in the gut, which may also be important. Aims: The aim of this randomized cross-over study was to further characterize the effect of low and high FODMAP intake on symptoms and the metabolome. Methods: In this longitudinal IBS (Rome IV) study, patients underwent 4 assessments: two non-intervention periods including a 1-week 'baseline' and 3-week 'run-in', followed by two dietary interventions, a low- and high-FODMAP diet, given in random order for 3-weeks each. Patients were provided detailed dietary instruction by a specialized dietitian at the start of each diet and advised that either diet may have therapeutic potential. At the end of each of the 4 periods, patients completed a 7-day food diary, the IBS Severity Scoring System (IBS-SSS), the quality-of-life (QOL) Nepean Dyspepsia index (SF-NDI), and provided fasting urine samples. Identification and quantification of 117 urine metabolites was performed using LC-MS. Questionnaires were analyzed by one-way ANOVA with Bonferroni, and metabolomics by multivariate analysis. Results: Ten female patients completed the study for this interim analysis (7 IBS-D, 2 IBS-C, 1 IBS-M). Dietary data showed good compliance with the interventions (Table 1). Symptoms were stable between the non-intervention time points, significantly reduced with the low FODMAP diet ( p =0.00), and a trend was seen between the low and high FODMAP diets ( p =0.07). The urinary metabolite levels in patients on the low FODMAP diet differed significantly from baseline, the main metabolites responsible for the change were phosphatidylcholines (e.g. PC40:2AA, PC36:0AA, LYSOC18:2). There was also a shift in the metabolome between the low and high FODMAP diets, the most significantly changed metabolites were sphingomyelins (SM 20:2), phosphatidylcholines (LYSOC20:4, PC40:6AE), and acylcarnitines (C18:1OH). Conclusions: This study showed that IBS symptoms were stable over 3 weeks and lowering dietary FODMAPs significantly improved symptoms. The diets caused a shift in the metabolome, but greater numbers of patients are needed to determine the complete metabolomic profile and their potential physiological significance in symptom responses. Funding Agencies: CIHRCanadian Nutrition Society